THE ANALYSIS STUDY OF ASSOCIATION OF PHARMACOLOGICAL TREATMENTS WITH LONG-TERM PAIN CONTROL IN PATIENTS WITH KNEE OSTEOARTHRITIS : A COMPREHENSIVE SYSTEMATIC REVIEW - Yulanda Putra, Yosie; Tri Lestari, Deby; Saputra, Zikri; Merisa Liona, Bella (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: Knee osteoarthritis (KOA) is a degenerative joint disease affecting 10 of males and 13 of women aged 60 or older. It causes joint discomfort, weakened muscles, and physical limitations. Treatment consists of surgical and non-surgical approaches, with knee arthroplasty being the most successful. Non-regenerative therapies like ozone, corticosteroids, and prolotherapy are popular but short-lived. Chinese herbal medicine (CHM) is widely used to treat KOA, targeting specific biological processes associated with the disease. Methods: Following PRISMA 2020 guidelines, this systematic review concentrated on full-text English literature published between 2014 and 2024. Editorials and review articles that appeared in the same journal as the submission were not accepted without a DOI. A number of websites, including ScienceDirect, PubMed, and SagePub, were utilized to gather the literature. Result: The study looked at more than 200 publications using reputable sources including Science Direct, SagePub, and PubMed. After it was decided that eight publications needed greater investigation, a more extensive review of the entire literature was carried out. Conclusion: Knee osteoarthritis is a common disease affecting middle-aged and elderly individuals. Platelet-rich plasma (PRP) injections, combined with hyaluronic acid, can alleviate knee pain and improve function. However, the efficacy varies depending on the formulation. Traditional Chinese herbal medicine has shown potential in treating KOA, but its effectiveness and safety remain debatable due to limited clinical trials and methodological rigor